Constructing epistemic landscapes: Methods of GIS-based mapping - Hans-Dieter Evers; Sven Genschick; Benjamin Schraven (University of Bonn, Center for Development Research (ZEF), 2009)
In this paper we have demonstrated how knowledge attributes of various kinds can be made visible in a knowledge map. Knowledge is not evenly distributed in space but shows discontinuities, gaps and heights. We use the concept of 'epistemic landscape' to allude to the complex tapestry of knowledge assets, institutions, organisations, hubs and clusters. Since antiquity maps have been used to provide orientation and direction. Moreover they 'can bridge the gap between language and culture in terms of communicating' (Hatfield, 2006). Maps are thus powerful tools in aid of decision making, proper planning and resource allocation. They are put into practice by indicating 'how to get from here to there'. They are in themselves repositories of knowledge, which can be retrieved and put into action. Epistemic landscapes and knowledge maps are therefore important parts of any information system. By additionally computing statistical measures of the density of knowledge clusters, comparative data can be interpreted. By correlating indicators, i.e. on knowledge output (like research papers or patents) with our knowledge density measure, the effectiveness of knowledge clustering can be studied. So far a similar approach has been used to study the competitive advantage of regions, following the earlier studies of Porter and others (Porter 1990; Sölvell 2009). Last not least we refer to the didactic value of maps. Information and knowledge, in our case the potential use of knowledge for development, have to be distributed to those that either benefit or suffer from the application of knowledge for development. The concept of epistemic landscapes and maps showing the complex and complicated business of producing and using knowledge enhance, we believe, the chances of government agencies, companies and civic organisations to understand and use knowledge for development.
Keywords: 330